Scoping review of the emerging definition of long COVID: implications for future research and clinical practice. - Salas, Roxana De Las; De la Asunción, Maira; Vásquez-Soto, Claudia; Orta-Visbal, Kevin; Serrano, Vanessa; Villarreal, Elizabeth; Sepúlveda, Sharell; Montalvo, María José; Nuñez, Jose Atilio; Borja, Juana (Revista de Salud Pública)
Introduction Long COVID, Post-COVID19 syndrome and prolonged COVID-19, are concepts classified as the set of signs and symptoms that persist after an acute episode of COVID-19 disease. Objective To describe what definitions have been published for the term "long COVID". Methods The PRISMA ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) was used as a base for a scoping review, as suggested by Joanna Briggs Institute. A search of databases, Medline via PubMed, Embase, SciELO and The Cochrane Library was undertaken. The data registry and synthesis of the results was carried out independently by two reviewers. Results Following removal of duplicates, 896 articles were retrieved of which 91 met the eligibility principles and 51 of which included a definition. At least four characteristics of the definitions were identified: time or term, organs affected, symptoms and clinical manifestations. Conclusions The review identified many concepts and definitions of "long COVID". These findings show that there is lack of consensus on the definition of long COVID-19.